THE LIMITS OF THE STANDARD MODEL ABOUT THE SEMANTIC FACTOR IN ANALOGICAL MAPPING - Minervino, Ricardo A.; Aldrover, J. Fernando; De la Fuente Arnanz, Javier (Anales de Psicología / Annals of Psychology, 2006)
We argue that the treatment given to semantics by the standard programs of analogical mapping (e.g., SME) reduces semantics to the influence of preestablished similarities between propositional elements on the mapping of these elements, and that the theoretical conception under this treatment supposes serious limits. We claim, in accordance with the High Level Perception Theory, that attempts to simulate analogical mapping should aim to equip programs with semantic abilities such as the detection of contextual similarities and the construction of analogue representations in response to mapping demands. We agree with the High Level Perception Theory in that programs like SME do not understand the analogies they produce, and in that they suppose a fallacious way of computational modeling. We argue that the responses given to the criticisms formulated by the High Level Perception Theory are not adequate, and that these criticisms deserve more attention in the field of analogical thinking.